Pelatihan Kesejahteraan Siswa Boarding School Untuk Penggalakan Kewirausahaan Minuman Telang - Bania, Allif Syahputra; Faridy, Najihatul; Chairuddin, Chairuddin; Nuraini, Nuraini; Akob, Bachtiar; Lubis, Nurliza; Al Tasa, Fiza Rauzika (LPPM Universitas Bumigora, 2025)
Community service is carried out for boarding school students at SMA Unggul Aceh Timur to have independence as the key to success in economic independence. The purpose of community service that will be carried out the form of several things given to partners such as the target of community service to be able to be independent in conducting micro-businesses related to telang drinks; partners will be introduced to insights related to procedures and information regarding processing and marketing telang drinks both offline and digital; telang drink products will be used by partners to be used for entrepreneurship as an additional little economy utilizing telang which is easy to cultivate in the partner's environment into ready-to-sell products and promising economy; the products produced are products that can be used for partners to be able to compete competitively regarding micro-scale packaged telang drinks. The uses a participatory action research approach. The stages begin with preparation, then continue with the implementation of community service, and continue with evaluation and material is presented in the form of lectures, demonstrations/practices and questions and answers/discussions. The results of the training evaluation were successful in encouraging telang drink entrepreneurship for boarding school students.